EVALUACIÓN TÉCNICA DEL SISTEMA DE ALUMBRADO PÚBLICO DE LA PARROQUIA EL GUAYACÁN DEL CANTÓN QUEVEDO - SANCHEZ PARRAGA , DANIEL ANTONIO (2025)
The public lighting system in the parish of El Guayacán has deficiencies that affect safety, energy efficiency, and the quality of life of its residents